MENINGKATKAN HASIL BELAJAR BIOLOGI MENGGUNAKAN LKS WORD SQUARE DISERTAI PRAKTIK LABORATORIUM DI MTs Al-ASROR TAHUN PELAJARAN 2011/2012 - Muarif, Moh. (UNIVERSITAS MUHAMMADIYAH METRO, 2012)
The aim of the research to implement of worksheet word square with laboratory practice are to improve study result of student in grade VIII at MTs Al-Asror year education 2011/2012 the subject matter living systems of plants. The method in this research was classroom action research and the subjeck of research is student at VIII MTS Al-Asror. The research indicated that more than 75 % student can finish the examinition. The data gaided by observation and tes technique, and then analysed by using discriptif data analysed technique. The result of the analysis, showed that aim of worksheet word square with laboratory practice are to increase the study result of student. Kata Kunci: model word square, praktik laboratorium, hasil belajar siswa.